Patterns of Cultivating Customs Towards Students Using Social Emotional Learning Methods In Boarding School Modern Darussalam Gontor For Girls Third Campus Karangbanyu Widodaren Ngawi - Moh. Ismail; Agnasalisa Inas; Ahmad Saifullah; Nurul Salis Alamin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
A person's personality is reflected in noble morals, he will lead a person to high dignity. In the Boarding School Modern Darussalam Gontor For Girls third campus, many things have been instilled about adab to the students with supporting factors of habituation, example, facilities, and reward punishment. As well as efforts to handle the inhibiting factors. The results of the research obtained are, the planting pattern carried out in Boarding School Modern Darussalam Gontor For Girls third campus is through learning materials and behavior based on dhomir and escort from educators. Factors supporting adab cultivation are example, discipline, facilities, and reward punishment. Meanwhile, the inhibiting factors are the background of the students in terms of economic, social, cultural, lack of knowledge of religious science, lack of awareness of young teachers due to age factors that should be a role model for students. Looking at some of the problems above, researchers concluded that the main reason for the failure to instill good morals in children is because of the unsuccess of educators, from parents, teachers, and the environment where children interact in emphasizing the importance of planting adab, therefore, it is important to understand the pattern of adab planting that has been applied in this cottage hopefully can make a foundation for educators in instilling adab to children from an early age. So from the results of this study in the form of adab planting patterns in Gontor Putri Tiga, and knowing what are the supporting and inhibiting factors. From these results, researchers hope that the pattern of planting adab in Boarding School Modern Darussalam Gontor For Girls third campus can be applied in the wider community, so that the purpose of planting adab can be realized.